The Influence of Word of Mouth and Tourist Attraction on Sustainable Tourism Development in Teluk Bicari, Kaimana Regency, West Papua - Mimi Selly; Damajanti Sri Lestari; Galuh Ajeng Ayuningtyas (International Journal of Business and Quality Research, 2026)
Tourism has become one of the strategic sectors contributing to regional economic growth while promoting environmental conservation and community welfare. However, sustainable tourism development depends not only on the attractiveness of tourist destinations but also on positive communication among visitors. This study aims to examine the influence of Word of Mouth and Tourist Attraction on Sustainable Tourism Development in Teluk Bicari, Kaimana Regency, West Papua. A quantitative approach with an explanatory research design was employed. Data were collected from 100 tourists using purposive sampling and analyzed using multiple linear regression with IBM SPSS Statistics 26. The findings indicate that Word of Mouth has a positive and significant effect on Sustainable Tourism Development (β = 0.263; t = 4.765; p < 0.001). Likewise, Tourist Attraction has a positive and significant effect (β = 0.770; t = 13.921; p < 0.001) and represents the most influential variable. Simultaneously, both independent variables significantly affect Sustainable Tourism Development (F = 117.200; p < 0.001). The coefficient of determination (R² = 0.707) indicates that 70.7% of the variation in Sustainable Tourism Development is explained by Word of Mouth and Tourist Attraction, while the remaining 29.3% is explained by other factors. These findings imply that strengthening destination attractiveness while encouraging positive visitor recommendations can effectively support sustainable tourism development in Teluk Bicari